2020
DOI: 10.1111/are.14790
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive characteristics and variations in the biochemical composition ofNeptunea arthritica cumingii crosse through embryonic development

Abstract: The copulation, egg laying, embryonic development and changes in amino acids and fatty acids in Neptunea arthritica cumingii during embryogenesis were studied to understand the embryo development process and nutritional requirements in the early life phase. The results showed that N. arthritica cumingii has direct development within the egg capsule and the development of embryos was classified into five stages: cleavage, egg swallowing, protoconch forming, shell development and juvenile. Embryos develop throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This carnivorous gastropod undergoes creeping metamorphosis and primarily preys on bivalves, particularly the horse mussel Modiolus 3 . Hao et al, (2020) divided the embryonic development process of N. cumingii into ve stages based on oocyst and egg characteristics, highlighting its direct development within the oocyst. Nutrients in the oocyst provide nutritional support for developing embryos 4 .…”
Section: Introductionmentioning
confidence: 99%
“…This carnivorous gastropod undergoes creeping metamorphosis and primarily preys on bivalves, particularly the horse mussel Modiolus 3 . Hao et al, (2020) divided the embryonic development process of N. cumingii into ve stages based on oocyst and egg characteristics, highlighting its direct development within the oocyst. Nutrients in the oocyst provide nutritional support for developing embryos 4 .…”
Section: Introductionmentioning
confidence: 99%
“…With adult whelk mainly in gravel and sand bottom, the bottom trawlers have been widely used to catch N. cumingii, resulting in a sharp decrease and threatened status of wild resources [3]. Consequently, to relieve stress of over shing and protect the wild resources, research on N. cumingii has been carried out, mainly focused on the feeding habits [5], the reproductive biology [1,6,7] and arti cial breeding [8].…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggested that the loci could be used as markers for population and kinship analyses in this species. Hao et al (2020) studied the copulation, egg laying, embryonic development and changes in amino acids and fatty acids in N.cumingii during embryogenesis to understand the embryo development process and nutritional requirements in the early life phase. whose results showed that N.cumingii had direct development within the egg capsule and the development of embryos was classified into five stages.…”
Section: Introductionmentioning
confidence: 99%